تصميم المواد التعليمية في درس اللغة العربية لتنمية مهارة القراءة - Aqif Khilmia (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
The University of Darussalam Gontor is a university that pays attention to learning Arabic. This is by the curriculum in each study program. As the founder stated that University must be a university that consistently teaches the language of the Qur`an, all students must master Arabic. However, the Islamic Economics study program does not yet have Arabic language teaching materials that have a bad impact on lecturers or students in the teaching and learning process. So, the researchers tried to compile Arabic language teaching materials specifically for students of Islamic Economics study programs at the University of Darussalam Gontor. The formulation of the research problem is “What the characteristics of Arabic teaching materials to improve reading skills of Islamic Economics study program students at the University of Darussalam Gontor?” and “How effective are Arabic teaching materials in improving reading skills of Management study students at the University of Darussalam Gontor?”. This study aims to explain the characteristics of the Arabic language teaching materials in improving the reading skills of students in Islamic Economics study programs at the University Darussalam of Gontor and to see the effectiveness of Arabic teaching materials to improve reading skills of students in Islamic Economics at the University of Darussalam Gontor. This research is a type of Research and Development (R & D) research which is preceded by data collection with interviews, tests, questionnaires, and documentation. To analyze the data collected, the author uses the t-test formula. The results of this study that teaching materials are arranged in the form of books, which are preceded by supervising for instructors of Arabic, learning steps, and syllabus. And the core of this book is material consisting of 13 chapters, consisting of reading texts and practice questions. At the end of this book, there are vocabulary words and their meanings arranged according to the alphabet. From the results of the pre-test and post-test values, it was found that the post-test value was greater than the pre-test. This shows that the compiled book is used both for students and instructors of Arabic. Then the Arabic language instructors must pay attention to the things students need to learn Arabic by looking at the condition of the students and their language skills. From the results of this discussion, researchers hope that lecturers of Arabic language material will always pay attention to the needs of students, so they can choose the right material and learning methods and according to their needs.